The Link Between Cognitive Strain and Ability to Perform Well in the Knowledge Work - Veteläinen, Juho-Matti Samuel (My University, 2023)
Working life has changed quite rapidly from manual work to knowledge work in the past decades. Due to the transition, companies are facing new kinds of challenges what comes to overall employee wellbeing. From the working ergonomics point of view the focus should be widened from the physical working ergonomics perspective also to cover the cognitive ergonomics, which is the most effective aspect of ergonomics for the knowledge workers, in a knowledge-intensive organizations. And as talking about the knowledge work, the cognitive strain has impacts on the working performance of knowledge workers. In this research, the goal is to build the link between the cognitive strain, and ability to perform well in the knowledge work. The study also aims to research cognitive ergonomics and how it could help in mitigating cognitive strain and enable knowledge workers to perform well. The cognitive strain has been observed via various factors of interruptions, disruptions, and information overload. Knowledge work performance has been defined based on the sources in the theory background as well as from the case company defined performance factors. The study findings show that the cognitive strain has an impact on the employee’s performance based on their own evaluation. The information overload was experienced as the most challenging, interruptions as secondly, and disruptions as the least severe source of cognitive strain. Also, cognitive ergonomics is seen as an interesting, but not so well-known topic among the interviewee respondents. The employees had built their own routines to mitigate the cognitive strain, but organizational-wide guidelines, for example for the remote work, would be appreciated by the interview respondents. The study contains solid theoretical background of the topic and extensive interview results, which leads to the discussions about the potential solutions to developing the cognitive ergonomics in the organization as well as suggestions for the future research identified during the study.

Työelämän muutos manuaalisesta työstä kohti tietotyöyhteiskuntaa on ollut nopeaa viime vuosikymmeninä. Nopean muutoksen vuoksi yritykset kohtaavat uudenlaisia haasteita työntekijöiden hyvinvointiin liittyen. Kokonaisvaltaisen työergonomian näkökulmasta tarkastelukulmaa olisi syytä laajentaa fyysisen ergonomian huomioimisesta myös kognitiivisen ergonomiaan, mikä on tärkeintä tietotyöntekijöille, jotka työskentelevät osaamisintensiivisissä organisaatioissa. Tietotyön kontekstissa kognitiivisella kuormituksella on vaikutuksia työntekijöiden työssä suoriutumiseen. Tässä Pro Gradu -tutkielmassa tavoitteena on yhdistää tietoa kognitiivisesta kuormituksesta sekä hyvästä suoriutumisesta tietotyössä. Tutkielma pyrkii myös selvittämään kognitiivisen ergonomian keinoja auttaa vähentämään kognitiivista kuormitusta ja edesauttaa tietotyöntekijöitä suoriutumaan hyvin työssään. Tutkielmassa kognitiivista kuormitusta on tarkasteltu keskeytysten, häiriötekijöiden ja tietotulvan eri konkreettisten ilmenemismuotojen kautta. Tietotyössä suoriutumisen määritelmä on tehty teoriataustassa käytettyjen lähteiden, sekä case-yritykselle toteutettujen haastattelujen vastausten perusteella. Tutkielman tulokset osoittavat, että haastateltujen tietotyöntekijöiden arvioiden mukaan kognitiivisella kuormituksella on vaikutusta työntekijöiden työssä suoriutumiseen. Haastateltavien keskuudessa tietotulva koettiin kaikkein ongelmallisimmaksi, keskeytykset toiseksi, ja häiriötekijät vähiten ongelmalliseksi kognitiivisen kuormituksen ilmenemismuodoksi. Kognitiivisen ergonomian käsite koettiin myös hyvin kiinnostavaksi haastateltavien keskuudessa, vaikka aihepiiri ei ollut entuudestaan tuttu. Haastateltavat tietotyöntekijät olivat rakentaneet omia rutiineita kognitiivisen kuormituksen ehkäisemiseksi, mutta koko organisaation kattava ohjeistus, esimerkiksi etätyöhön, olisi tervetullut haastateltavien näkökulmasta. Tutkielma koostuu teoriataustasta ja laajasta haastattelumateriaalista tuloksineen, joka johtaa pohdintaan mahdollisista ratkaisumalleista, joilla kehittää kognitiivsen ergonomian tasoa organisaatiossa. Tutkielman lopuksi on vielä jatkotutkimusehdotuksia, joita on tunnistettu tutkimusta tehdessä.
Keywords: ergonomics; knowledge work; cognitive ergonomics; knowledge management; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management